Kesahan Kandungan Instrumen Sikap Keusahawanan Dalaman ke Arah Kesediaan Penerapan Elemen Keusahawanan bagi Guru Pelatih TVET Berdasarkan Indeks Kesahan Kandungan (CVI) - Abdul Wahab, Zabidi; MD OSMAN, SITI ZURAIDAH; AHMAD, NOOR HAZLINA (Research and Innovation in Technical and Vocational Education and Training, 2025)
The internal entrepreneurial attitude of TVET trainee teachers can influence how well they are ready to apply entrepreneurial elements. Therefore, an instrument to measure internal entrepreneurial attitudes needs to be identified and validated. Content validity is a necessary method to assess the suitability of an instrument to be an effective measuring tool. This study utilised the Content Validity Index (CVI) method to assess the validity of the instrument content. The evaluated instrument contains 17 items based on three domains. A total of eight experts were selected through purposive sampling to participate in this study. The experts consisted of five professional experts in psychometrics, assessment, educational psychology, languages, and entrepreneurship and three lay experts who are practitioners of the application of entrepreneurial elements in their respective professional fields. Base on experts’ feedback, 15 items accepted together with one item modified while two items were rejected. The results of the study show the adapted instrument has relevant content validity and potentially can measure the internal entrepreneurial attitudes among TVET trainee teachers with S-CVI value of 0.93. Furthermore, further analysis and studies are proposed to evaluate the relationship and influence between internal entrepreneurial attitudes and the readiness to apply entrepreneurial elements.